Mortality After Paclitaxel-Coated Device Use in Dialysis Access: A Systematic Review and Meta-Analysis. (October 2019) - Dinh, Krystal; Limmer, Alexandra M.; Paravastu, Sharath C. V.; Thomas, Shannon D.; Bennett, Michael H.; Holden, Andrew; Varcoe, Ramon L.
Purpose: To report the risk of all-cause mortality in patients who underwent dialysis access treatment using paclitaxel-coated devices compared with percutaneous transluminal angioplasty (PTA) with an uncoated balloon.Materials and Methods: A systematic review and meta-analysis of randomized controlled trials were performed to investigate the mortality outcomes associated with paclitaxel-coated devices in the treatment of patients with a failing dialysis access (last search date February 28, 2019). The primary endpoint was all-cause mortality. This analysis included 8 studies comparing paclitaxel-coated balloon (PCB) angioplasty (n=327) and PTA (n=331) in the treatment of failing dialysis access. None investigated paclitaxel-coated stents. Mortality data were pooled using a random effects model. Statistical heterogeneity was evaluated with a chi-square test and the I 2 statistic. Summary statistics are expressed as relative risk ratios (RR) with a 95% confidence interval (CI).Results: At the pooled mean follow-up of 13.5 months (median 12, range 6–24) all-cause mortality was similar in the PCB group (13.8%) compared with PTA (11.2%; RR 1.26, 95% CI 0.85 to 1.89, p=0.25; I 2 =0%). Subgroup analysis, stratified according to length of follow-up, confirmed that there were no statistically significant differences in mortality at short- and midterm follow-up [6-month (8 studies): 5.2% vs 4.8%, RR 1.24, 95% CI 0.62 to 2.47, p=0.55; 12-month (6 studies): 6.3% vs 6.0%, RR 1.06, 95% CI 0.43 to 2.63, p=0.90; and 24-month (3 studies): 19.0% vs 13.5%, RR 1.38, 95% CI 0.90 to 2.12, p=0.14).Conclusion: The analysis found no difference in short- to midterm mortality among patients treated with a drug-coated balloon compared with PTA. With proven benefit and no evidence of harm, the authors recommend ongoing use of PCB for the failing dialysis access.